Photoactivatable RuII Complex Bearing 2,9‐Diphenyl‐1,10‐phenanthroline: Unusual Photochemistry and Significant Potency on Cisplatin‐Resistant Cell Lines - Mansour, Najwa (2018)
The current study investigates [Ru(bipy)2(dpphen)]Cl2 [where bipy = 2,2′‐bipyridine and dpphen = 2,9‐diphenyl‐1,10‐phenanthroline] (complex 1) for photoactivatable chemotherapy (PACT) application on five cancer cell lines. [Ru(bipy)2(phen)]Cl2 [where phen = 1,10‐phenanthroline] (complex 2) was included as an unstrained control. Upon excitation with visible light, complex 2 proved to be photostable while complex 1 underwent a quantitative dissociation of the bipy ligand and formation of a RuII polypyridyl aqua complex in water. Complex 1 demonstrated only marginal activity in the dark; its cytotoxicity increased significantly upon photoactivation with a high phototoxicity index (PI = [IC50 dark]/[IC50 light]) ranging from 39.2‐fold in A549 to over 100‐fold in MDA‐MB‐231. Complex 2, on the other hand, did not show much difference in anticancer activity between dark and light conditions. Importantly, the IC50 of the photoproduct of complex 1 was several folds lower than that of cisplatin in all tested cell lines. Furthermore, the dissociating ligand (bipy) was biologically inert in almost all cell lines investigated confirming that phototoxicity was mediated primarily by the Ru aqua complex that is released upon irradiation. In conclusion, the Ru‐centered complex 1 could represent a potential photoactivatable chemotherapeutic drug that increases selectivity to tumors and offers alternative treatment in the light of increasing cisplatin resistance.